2006
DOI: 10.1017/s0030605306001347
|View full text |Cite
|
Sign up to set email alerts
|

Rapid population declines and mortality clusters in three Oriental white-backed vulture Gyps bengalensis colonies in Pakistan due to diclofenac poisoning

Abstract: The population declines affecting Asian Gyps vultures are among the most rapid and geographically widespread recorded for any species. This paper describes the rates and patterns of mortality and population change over 4 years at three Oriental white-backed vulture Gyps bengalensis colonies in Pakistan: Dholewala (initially 421 pairs), Toawala (initially 445 pairs) and Changa Manga (initially 758 pairs). Vulture mortality led to the extirpation of two of these colonies (Changa Manga and Dholewala) in 3 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 12 publications
3
55
1
1
Order By: Relevance
“…Communal roost sites are also regularly used (Gilbert et al 2006). It breeds in colonies in tall trees such as Bombax ceiba and Ficus religiosa, often near human habitation (Paudel 2008;Baral 2010;IUCN 2012c).…”
Section: Species Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Communal roost sites are also regularly used (Gilbert et al 2006). It breeds in colonies in tall trees such as Bombax ceiba and Ficus religiosa, often near human habitation (Paudel 2008;Baral 2010;IUCN 2012c).…”
Section: Species Distributionmentioning
confidence: 99%
“…The global population is estimated to be about 45,000 mature individuals (Birdlife International 2012). (Gilbert et al 2006;Prakash et al 2007;Pain et al 2008;Chaudhary et al 2012 Slender-billed Vulture (Fig. 4) Slender-billed Vultures range through southern Nepal.…”
Section: Species Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in Nepal, India and Pakistan show three species of resident Gyps vulture (White-rumped Gyps bengalensis, Long-billed Gyps indicus and Slender-billed Vulture Gyps tenuirostris) have undergone >97% population declines (Baral et al 2004, Prakash et al 2007. Studies conducted in Pakistan showed the complete loss of a large breeding colony of White-rumped Vulture within a short period of 2001 to 2003 (Gilbert et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There has been drastic decline in the vulture population in Indian sub-continent over last two decades (Rahmani, 1998;Prakash, 1999;Prakash and Rahmani, 1999;Virani et al, 2001;Prakash et al, 2003;Chhangani, 2005;Gilbert et al, 2006). Since 1996, the breeding ecology and population of vulture study in and around Jodhpur and in the Thar desert have been examined by monitoring the nesting site, making censuses, recording predation, observing inter-species interaction and locating seasonal migration (Chhangani and Mohnot, 2004;Chhangani, 2002aChhangani, , b, c, 2005Chhangani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%